A system architecture and implementation of simulation-based optimisation approach to improve airport surface operations. (1st January 2014) - Wei, Wenbin; Davis, Lawrence; Fu, Chunsheng; Cheng, Victor H.L.; Seo, Anthony Y.; Cao, Shuo
The system architecture and implementations of a simulation-based optimisation approach to improve airport surface operations is introduced in this paper. We consider airport surface operations, including gate operations, taxiing on taxiways, and runway operations, as an integrated problem. The architecture consists of two major components: a fast-time simulator and an optimiser. A fast-time simulator is built to evaluate the feasibility and performance of solutions generated from the optimiser. The core component of the optimiser is the genetic algorithm. A shortest-path routing algorithm and some heuristic scheduling algorithms are also embedded in the optimiser. Our proposed simulation-based optimisation approach is applied to the case studies of the east side of the Dallas-Fort Worth (DFW) airport. Initial results have demonstrated the usefulness and benefit of our optimisation approach for improving airport surface operations.